HUBUNGAN STATUS EKONOMI TERHADAP PERNIKAHAN DINI PADA PEREMPUAN DI PERDESAAN INDONESIA - Ratna Dwi Wulandari; Agung Dwi Laksono (JURNAL KESEHATAN REPRODUKSI, 2020)
Abstract Background: Early marriage practice in Indonesia is more often found in rural than in urban areas. Objective: The aim of this study is to examine the relationship of socioeconomic status and early marriage in rural areas in Indonesia. Method: This study used data from the 2017 Indonesian Demographic Health Survey. The sample was 2,252 of women aged 19 – 24 living in rural Indonesia. The variables included in the analysis were early marriage status, socioeconomic status, educational level, and working status. Analysis of collinearity, chi-square, and multiple logistic regressions were conducted in this study. Results: The socioeconomic status and educational level were significantly associated with early marriage among women aged 19 – 24 in rural Indonesia. The poorest socioeconomic women were 2.23 times more likely to experience early marriage than the richest women. Poorer women were 1.68 times more likely to experience early marriage than the richest women. Women who did not go to school, having primary to secondary level of education were more likely to experience early marriage than those having tertiary level, constituting for 10.34 times, 12.10 times and 4.52 times, respectively. Educational level was more dominant in relation to early marriage than socioeconomic status. Conclusion: Socioeconomic status and educational level are associated with early marriage. Poor young women with low educational level in rural areas should be the focus of the program target to reduce the coverage of early marriage in Indonesia. Keywords: Rural area, Women, Early marriage, Socioeconomic.   Abstrak Latar belakang: Praktik pernikahan dini di Indonesia lebih sering ditemukan di wilayah perdesaan dibandingkan perkotaan. Tujuan: Studi ini bertujuan untuk menganalisis hubungan status sosioekonomi terhadap kejadian pernikahan dini di perdesaan di Indonesia. Metode: Studi ini menggunakan data Survei Demografi Kesehatan Indonesia tahun 2017. Sampel yaitu 2.252 perempuan 19 – 24 tahun yang tinggal di perdesaan Indonesia. Variabel yang dianalisis meliputi pernikahan dini, status sosioekonomi, tingkat pendidikan, dan status bekerja. Analisis yang digunakan yaitu uji collinearity, chi-square, dan regresi logistik ganda. Hasil: Status sosioekonomi dan tingkat pendidikan berhubungan secara signifikan dengan pernikahan dini pada perempuan 19 – 24 tahun di perdesaan Indonesia. Perempuan paling miskin memiliki kemungkinan lebih tinggi 2,23 kali untuk mengalami pernikahan dini dibandingkan perempuan paling kaya. Perempuan miskin memiliki kemungkinan lebih tinggi 1,68 kali mengalami pernikahan dini dibandingkan perempuan paling kaya. Perempuan yang tidak sekolah, pendidikan SD-SLTP, dan SLTA memiliki kemungkinan lebih tinggi mengalami pernikahan dini dibandingkan lulusan perguruan tinggi, berturut-turut sebesar 10,34 kali, 12,10 kali, dan 4,52 kali. Faktor tingkat pendidikan lebih dominan hubungannya dengan pernikahan dini dibandingkankan dengan faktor status sosioekonomi. Kesimpulan: Status sosioekonomi dan tingkat pendidikan berhubungan dengan pernikahan dini. Remaja putri miskin dengan tingkat pendidikan rendah di perdesaan harus menjadi fokus sasaran program penurunan cakupan pernikahan dini di Indonesia. Kata Kunci: Perdesaan, Perempuan, Pernikahan dini, Sosioekonomi.